PERCEPÇÃO E ATUAÇÃO DA EQUIPE DE ENFERMAGEM FRENTE AO RECÉM-NASCIDO PRÉ-TERMO DESORGANIZADO - Nascimento, Lílian do; Rosa, Ana Cristina de Oliveira; Lopes, Carlos Augusto; Urzedo, Jane; Pacheco, Zuleyce Maria Lessa; Salimena, Anna Maria de Oliveira (Revista Baiana de Enfermagem‏, 2014)